ICT, access to services and wage inequality - Hildegunn Kyvik Nordås (World Trade Organization (WTO), 2004)
This paper discusses how information and communication technology (ICT) affects the quality and reach of consumer services. These services need to be provided locally, but consist of several components, some of which can be digitised and transmitted over long distances. A general equilibrium model is developed and numerical simulations in a stylised two-factor, two-region, centre-periphery setting are presented. Trade in intermediate services improves the quality of consumer services enormously in the periphery, but may reduce the quality at the centre. Trade in intermediate services also has a dramatic impact on skilled workers' wages in the periphery, both relative to unskilled workers in their own region and relative to skilled workers at the centre and leads to a more equal distribution of income both between the centre and the periphery and within the periphery.
Keywords: D23; F12; F13; R12; R13; 330; Trade in services; transaction costs; income distribution; ICT